GAMBARAN KESIAPAN MAHASISWA KEPERAWATAN TINGKAT AKHIR UNIVERSITAS UDAYANA DALAM MENGHADAPI PROFESI NERS DI MASA PANDEMI COVID-19 - Lesmana, Ellang Fauzian; Sawitri, Ni Komang Ari; Swedarma, Kadek Eka (Coping: Community of Publishing in Nursing; Vol 12 No 3 (2024): Juni 2024DO - 10.24843/coping.2024.v12.i03.p12, 2024)
The COVID-19 pandemic has had an impact on changes in the learning methods of nursing students at Udayana University. Changes in learning methods with the blended system require students at the academic stage to be able to adapt so that it can affect their readiness to continue on the nursing profession stage. The purpose of this study is to describe the readiness of Udayana University final-level nursing students in facing the nursing profession during the COVID-19 pandemic. This study uses a quantitative descriptive design. A total of 60 final year 2018 students was involved as participants in readiness to face the nursing profession using the total sampling technique. The results showed that most of the respondents from the age range of 21 years to 23 years showed that the majority of respondents aged 22 years were 34 people (56.7%) and the majority of respondents were women as many as 50 people (83.3%). The majority of respondents had a readiness level in the ready category, namely 54 respondents (90%). Further research is expected to increase their readiness before continuing the nursing profession by attending nursing profession seminars to increase motivation and knowledge.